2019
DOI: 10.1111/jce.14182
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage closure: A therapy uniquely suited for specific populations of patients with atrial fibrillation

Abstract: Atrial fibrillation (AF) is the most common clinically relevant arrhythmia and confers a fivefold increased risk for stroke. Cardioembolic stroke secondary to AF is a devastating event, but is largely preventable with appropriate oral anticoagulation (OAC). The PROTECT and PREVAIL trials demonstrated that the WATCHMAN left atrial appendage closure (LAAC) device in combination with short‐term warfarin therapy is noninferior to long‐term warfarin with respect to a composite endpoint of stroke, cardiovascular dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 68 publications
(168 reference statements)
0
10
0
Order By: Relevance
“…Such patients consistently exhibit low rates of stroke and major bleeding events. Therefore, LAAO is suitable for patients contraindicated for oral anticoagulants, end-stage renal disease, recurrent gastrointestinal hemorrhage, and prior intracranial hemorrhage (Black-Maier et al, 2019). Here, we performed a meta-analysis to determine the efficacy and safety of LAAO in CKD patients with AF.…”
Section: Introductionmentioning
confidence: 99%
“…Such patients consistently exhibit low rates of stroke and major bleeding events. Therefore, LAAO is suitable for patients contraindicated for oral anticoagulants, end-stage renal disease, recurrent gastrointestinal hemorrhage, and prior intracranial hemorrhage (Black-Maier et al, 2019). Here, we performed a meta-analysis to determine the efficacy and safety of LAAO in CKD patients with AF.…”
Section: Introductionmentioning
confidence: 99%
“…Our study consisted mainly of patients with LAAC before 2018. With the increase in the number of LAAC, the likelihood of adverse events occurring during the perioperative period normally decreases, even in elderly patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the e cacy of LAAC in AF patients who had a prior bleeding, there were several small sample studies which reported the effectiveness and safety of LAAC [31][32][33][34]; however, none of them focused on comparing the difference in e cacy of LAAC between patients with and without prior bleeding. Our study compared the extent of RRR in thromboembolic events and major bleeding attributed to LAAC strategy between patients with and without a history of prior bleeding.…”
Section: Discussionmentioning
confidence: 99%